HUBUNGAN USIA MELAHIRKAN TERAKHIR, PEMAKAIAN KONTRASEPSI, PARITAS DAN MENARCHE DENGAN MENOPAUSE - Bela Purnama Dewi; Novita Mustika Buana (Jurnal Kesehatan dan Pembangunan, 2024)
Menopause is a natural phase experienced by a woman, the cessation of the menstrual cycle. The aim of this study was to determine whether there was a relationship between age at last birth, history of contraceptive use, parity and menarche and menopause. The analytical method used is a cross sectional approach. The sampling technique was a total sampling of 48 respondents. Analysis uses the Chi-square statistical test. The results of this study showed that there were 39 respondents with normal menopause age (81.3%), 29 respondents with a birth age of ?35 years (60.4%), 32 respondents (66.7%) using non-hormonal contraception. , respondents with parity > 2 people were 25 respondents (52.1%). The results of the bivariate analysis showed that there was a relationship between age at last birth (p value = 0.020 <? = 0.05), contraceptive use (p value 0.044 <? = 0.05), parity (p value 0.028 <?=0.05) , and menarche (p value 0.003<?=0.05) with age at menopause in Talang Jambe Village, Palembang. The results of multivariate analysis show that menarche is the factor that most influences menopause ? value = 0.008. The OR value of menarche is 61.817. It is recommended for health workers to further improve health services and education about menopause.